Testing the New Keynesian Model on U.S. and Euro Area Data - Mikael Juselius (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
I apply the Johansen and Swensen (1999, 2004) method of testing exact rational expectations within the cointegrated VAR (Vector Auto-Regressive) model, to testing the New Keynesian (NK) model. This method permits the testing of rational expectation systems, while allowing for non-stationary data. The NK-model is tested on quarterly U.S. and Euro area time series data. I find that the restrictions implied by the core equations of the NK-model are rejected regardless of sample periods or measures of real marginal costs. I also provide a tentative explanation of the results favored by previous researches.
Keywords: C52; E52; E31; C32; 330; New Keynesian Phillips curve; cointegration; vector autoregressive model; New-Keynesian Phillips Curve; Rationale Erwartung; Kointegration; VAR-Modell; Schätzung; USA; EU-Staaten